About the First Performances of Works by Uzbek Composers for Piano - qizi, Tuychiyeva Oydinoy Zulfiqor (International Journal on Orange Technologies, 2023)
This article is devoted to the problem of interpreting piano works by Uzbek composers. It deals with the issues of first reading of domestic works, the author's performance, the tandem "performer-composer" in modern realities.